Cell cycle, telomeres, and telomerase in leishmania spp.: What do we know so far? - Assis, Luiz H. C. [UNESP]; Andrade-Silva, Débora [UNESP]; Shiburah, Mark E. [UNESP]; de Oliveira, Beatriz C. D. [UNESP]; Paiva, Stephany C. [UNESP]; Abuchery, Bryan E. [UNESP]; Ferri, Yete G. [UNESP]; Fontes, Verônica S. [UNESP]; de Oliveira, Leilane S. [UNESP]; da Silva, Marcelo S. [UNESP]; Cano, Maria Isabel N. [UNESP] (MDPI, 2021)
Leishmaniases belong to the inglorious group of neglected tropical diseases, presenting different degrees of manifestations severity. It is caused by the transmission of more than 20 species of parasites of the Leishmania genus. Nevertheless, the disease remains on the priority list for developing new treatments, since it affects millions in a vast geographical area, especially low-income people. Molecular biology studies are pioneers in parasitic research with the aim of discovering potential targets for drug development. Among them are the telomeres, DNA–protein structures that play an important role in the long term in cell cycle/survival. Telomeres are the physical ends of eukaryotic chromosomes. Due to their multiple interactions with different proteins that confer a likewise complex dynamic, they have emerged as objects of interest in many medical studies, including studies on leishmaniases. This review aims to gather information and elucidate what we know about the phenomena behind Leishmania spp. telomere maintenance and how it impacts the parasite’s cell cycle.
Keywords: Cell cycle; Leishmania spp; Leishmaniases; Telomerase; Telomeres